Effect of solvent variation on results of antibiotic susceptibility test using the disk diffusion method against Staphylococcus aureus - Firda Nurul Habibah; Hafizah Ilmi Sufa; Iis Kurniati; Zuri Rismiarti (Current Biomedicine, 2025)
Background Mueller-Hinton agar (MHA) is widely used for disk diffusion tests to assess antibiotic susceptibility in non-fastidious bacteria. The type of water used to prepare the MHA may have affected the test outcomes.